A composite preparation process for enhancing the mechanical properties of marine laminated wood

Through the composite preparation process, the basalt fibers and nanotitanium dioxide are modified and combined with wood powder and epoxy resin are heat-pressed to form, which solves the problems of poor antibacterial performance and poor mechanical properties of marine laminated wood, and achieves higher mechanical properties and antibacterial properties.

CN118725596BActive Publication Date: 2025-02-07JIANG SU GUANG JIA XIN CAI LIAO KE JI YOU XIAN GONG SI

Patent Information

Application Number
CN202410750685.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-02-07
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing marine laminated wood has poor antibacterial properties and poor mechanical properties, making it difficult to meet the long-term use needs of ships.

Method used

Using a composite preparation process, the basalt fibers and nanotitanium dioxide are dispersed by ultrasonication and multi-step modification treatment, including amyotrophy, isocyanate modification, grafting reaction and antibacterial modification, and finally the modified basalt fibers and wood are dispersed. The powder, epoxy resin and other combinations are combined to perform hot pressing molding.

Benefits of technology

It significantly enhances the mechanical properties and antibacterial properties of laminated wood, and improves its stability and service life in humid and corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004887812270000141
    Figure BDA0004887812270000141
  • Figure BDA0004887812270000151
    Figure BDA0004887812270000151
Patent Text Reader

Abstract

The invention relates to the technical field of composite material preparation, and specifically discloses a composite preparation process for enhancing the mechanical properties of marine laminated wood. Wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, a stabilizer and a curing agent are uniformly mixed, kneaded in an open mill, and hot-pressed in a hot press to obtain the marine laminated wood. The antibacterial modified basalt fiber-titanium dioxide contains a large number of active groups, which can form a three-dimensional staggered support network in a matrix, generate a cross-linked network structure, and effectively improve the mechanical properties of the matrix. The epoxy resin is used as an adhesive with strong bonding force, and can tightly bond the wood powder and other materials together, thereby reducing the waste of wood and improving the utilization rate of wood to achieve environmental benefits, forming a laminated wood with stable structure and high strength. Through a curing cross-linking reaction, a mesh structure can be formed, which further enhances the overall mechanical strength of the laminated wood and prolongs its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation, in particular to a composite preparation process for enhancing the mechanical properties of marine laminated wood. Background Art

[0002] Laminated wood, also known as plywood or laminated wood, is a board made of multiple layers of thin wood chips or wood fibers glued together. It has excellent mechanical and processing properties, and has the characteristics of high strength, not easy to deform, wear resistance, and water resistance. It is widely used in the fields of ships, vehicles, construction, and furniture manufacturing. Among them, marine laminated wood is mostly used for LNG ships and LPG ships. It is laid on the independent liquid cargo tanks and supporting steel structures of liquid cargo transport ships. On the one hand, it must withstand the mechanical load from the liquid cargo tanks, and on the other hand, it must load low-temperature goods. Therefore, laminated wood is required to be much stronger and more rigid than ordinary wood. Traditional marine laminated wood is mostly made of natural wood as raw material, but the antibacterial and anti-corrosion effect of wood is general. It is more likely to breed bacteria in a humid environment for a long time, causing corrosion to the hull, mildew and rot, and shortening the service life of the hull. In order to meet the needs of long-term use of ships, the comprehensive performance requirements of marine laminated wood are very high.

[0003] Chinese patent application CN117844187A discloses a composite laminated wood for LNG ships, wherein the raw materials of the laminated wood include epoxy resin, curing agent, reinforcing material, hollow microsphere filler and coupling agent, and the preparation of the laminated wood has the characteristics of low cost, short delivery cycle, light weight, low thermal conductivity, environmental protection, and easy transportation and storage. However, the dispersion of each raw material in the laminated wood is general, which has a certain influence on the mechanical properties of the composite material, and the vertical mechanical properties are not good, and the antibacterial properties are poor. Chinese patent application CN116218141A discloses a lightweight epoxy resin substitute wood, wherein fillers such as photoinitiator, thermal initiator and hollow glass microsphere are introduced into the epoxy resin, and the polymerization reaction is initiated by ultraviolet light, and the resin mixture is cured, which greatly shortens the curing cycle of the substitute wood, and the maximum temperature of the curing process is low, but the epoxy resin substitute wood uses hollow glass microspheres as fillers in the preparation process, which will reduce the strength and toughness of the material and increase the difficulty of processing. At the same time, the hollow glass microspheres have poor dispersion, which easily leads to poor mechanical properties and poor antibacterial properties. Chinese patent application CN109731747A discloses a method for preparing an anticorrosive and antibacterial wood fiber composite material, wherein the surface of the wood fiber composite material is treated by spraying a nano oxide suspension, a polydimethylsiloxane treatment liquid, and a nano oxide suspension to improve the flame retardant, smoke suppression, anticorrosive and antibacterial properties of the composite material, enhance the hydrophobicity of the composite material surface, block moisture from entering the interior of the composite material, destroy the living environment of microorganisms, and significantly improve the service life and anticorrosive and antibacterial durability of the wood, but the mechanical properties of the wood are average. Therefore, it is of great significance to develop a laminated wood with excellent mechanical properties and good antibacterial properties. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies of the prior art, the present invention provides a composite preparation process for enhancing the mechanical properties of marine laminated wood, thereby solving the problems of poor antibacterial properties and poor mechanical properties of marine laminated wood.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the present invention discloses a composite preparation process for enhancing the mechanical properties of marine laminated wood, comprising the following steps:

[0008] Step 1: Ultrasonically disperse the basalt fiber in a mixed solvent, add γ-aminopropyltriethoxysilane after uniform dispersion, stir and mix, react at 25-35° C. for 2-5 hours, filter after the reaction, wash with anhydrous ethanol, and dry at 60° C. for 12 hours to obtain amino basalt fiber;

[0009] Step 2: Ultrasonic dispersion of nano titanium dioxide in N,N-dimethylformamide, after uniform dispersion, add 1,8-diisocyanate and dibutyltin dilaurate (DBTDL), stir and mix, react, centrifuge after the reaction, the centrifugal speed is 8000r / min, the centrifugal time is 5min, wash with anhydrous ethanol, vacuum dry at 60°C for 8h, and obtain isocyanate-modified titanium dioxide;

[0010] Step 3: ultrasonically disperse the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, heat up, react, filter after the reaction, wash with anhydrous ethanol, and vacuum dry at 60° C. for 12 h to obtain basalt fiber grafted titanium dioxide;

[0011] Step 4: Ultrasonic dispersion of basalt fiber grafted titanium dioxide in N,N-dimethylformamide, after uniform dispersion, adding p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI), 1-hydroxybenzotriazole (HOBT) and triethylamine (TEA), mixing evenly, reacting, after the reaction is completed, filtering, washing with dichloromethane, and vacuum drying at 60° C. for 8 h to obtain chloromethyl modified basalt fiber-titanium dioxide;

[0012] Step 5: ultrasonically disperse the chloromethyl modified basalt fiber-titanium dioxide in acetone, and after uniform dispersion, add dimethylaminoethyl methacrylate, heat up, react, and after the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60° C. for 8 hours to obtain antibacterial modified basalt fiber-titanium dioxide;

[0013] Step 6: Evenly mix the wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, stabilizer and curing agent, knead them in an open mill, and after evenly mixing, perform hot pressing molding in a hot press, cool and demold to obtain marine laminated wood.

[0014] Preferably, the mixed solvent in step 1 is a mixture of anhydrous ethanol and deionized water in a mass ratio of 4:1.

[0015] Preferably, in step 1, the mass ratio of the mixed solvent, basalt fiber and γ-aminopropyltriethoxysilane is 2400-3500:100:48-55.

[0016] Preferably, in the step 2, the mass ratio of nano-titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2100-2500:95-115:1-1.6.

[0017] Preferably, the reaction temperature in step 2 is 90-110° C., and the reaction time is 8-10 h.

[0018] Preferably, in step three, the mass ratio of the amino basalt fiber, isocyanate-modified titanium dioxide, and N,N-dimethylformamide is 100:72-95:2400-3200.

[0019] Preferably, the reaction temperature in step 3 is 90-105° C., and the reaction time is 6-9 h.

[0020] Preferably, in step 4, the mass ratio of basalt fiber grafted with titanium dioxide, N,N-dimethylformamide, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole, and triethylamine is 100:3500-4500:15-25:5-9:2-6:38-60.

[0021] Preferably, the reaction temperature in step 4 is 65-75° C., and the reaction time is 18-24 h.

[0022] Preferably, in the step five, the mass ratio of chloromethyl modified basalt fiber-titanium dioxide, acetone, and dimethylaminoethyl methacrylate is 100:2100-2500:48-60.

[0023] Preferably, the reaction temperature in step 5 is 50-60° C., and the reaction time is 15-18 h.

[0024] Preferably, in step six, the mass ratio of wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, stabilizer and curing agent is 100:35-55:5-12:1-2:30-48.

[0025] Preferably, in the open mill in step 6, the kneading temperature is 120-135°C, the kneading time is 15-30min, the hot pressing temperature is 170-180°C, the hot pressing time is 5-8min, and the hot pressing pressure is 8MPa during the hot pressing process.

[0026] Preferably, in step six, the stabilizer is a calcium-zinc composite stabilizer, and the curing agent is hexamethyltetramine.

[0027] (III) Beneficial technical effects

[0028] (1) In the present invention, γ-aminopropyltriethoxysilane is first used to modify basalt fiber, and amino groups are introduced on the surface of basalt fiber to obtain amino basalt fiber. Nano-titanium dioxide is modified by using 1,8-diisocyanate. The isocyanate group at one end of 1,8-diisocyanate reacts with the hydroxyl group on the surface of nano-titanium dioxide to obtain isocyanate-modified titanium dioxide. Long-chain alkyl and isocyanate groups are introduced on the surface of nano-titanium dioxide. The amino groups on the surface of basalt fiber react with the isocyanate groups on the isocyanate-modified titanium dioxide to introduce a large number of imine groups to obtain basalt fiber grafted titanium dioxide. The imine on the rock fiber grafted titanium dioxide and the carboxyl group on the chloromethylbenzoic acid undergo amidation reaction under the action of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine (TEA) to obtain chloromethyl modified basalt fiber-titanium dioxide. The chloromethyl on the chloromethyl modified basalt fiber-titanium dioxide reacts with dimethylaminoethyl methacrylate to introduce quaternary ammonium salt to obtain antibacterial modified basalt fiber-titanium dioxide. Wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, stabilizer and curing agent are evenly mixed, kneaded and then hot-pressed to obtain marine laminated wood.

[0029] (2) The basalt fiber used in the present invention has excellent insulation, mechanical properties and acid and alkali corrosion resistance. After being mixed with wood powder, the basalt fiber is embedded in the laminated wood, which can significantly enhance the structural strength of the laminated wood, improve the mechanical properties of the laminated wood, and be more stable when subjected to external forces, and is not easy to deform and damage. The introduced nano-titanium dioxide has excellent antibacterial and anti-mildew effects. Adding it to the laminated wood can effectively inhibit and kill bacteria and improve the antibacterial properties of the laminated wood. Furthermore, the nano-titanium dioxide can also utilize its photocatalytic properties to catalyze organic pollutants under light conditions, decompose organic pollutants, and reduce air pollution. It has excellent ultraviolet shielding properties, which can enhance the anti-ultraviolet ability of the laminated wood, extend the service life of the laminated wood, and maintain its color stability, improve the weather resistance and chemical stability of the laminated wood, so that it can maintain good performance in various environments. The introduction of quaternary ammonium salts, the cations on the quaternary ammonium salts can be adsorbed on the cell membrane surface of negatively charged bacteria, changing the permeability of the bacterial cell wall, causing an imbalance in the cell membrane charge, effectively killing bacteria, and having a good inhibitory effect on the growth of Staphylococcus aureus and Escherichia coli. It is evenly dispersed inside and outside the laminated wood to achieve comprehensive antibacterial and mildew resistance. At the same time, the introduction of antibacterial ingredients through chemical grafting can effectively reduce the precipitation of antibacterial ingredients, improve the antibacterial durability, and further increase the service life of the laminated wood.

[0030] (3) In the present invention, nano-titanium dioxide is grafted onto basalt fiber, which effectively avoids the agglomeration of nano-titanium dioxide. At the same time, the antibacterial modified basalt fiber-titanium dioxide obtained contains a large number of active groups, which can form a three-dimensional staggered support network in the matrix and produce a cross-linked network structure. Through the synergistic effect of nano-titanium dioxide and basalt fiber, the mechanical properties of the matrix are effectively improved. At the same time, it has excellent compatibility and improves the density of laminated wood. The long-chain alkyl introduced during the reaction process can further improve the toughness of the matrix and improve the bending performance, which can be better used in marine applications.

[0031] (4) The epoxy resin in the present invention has excellent mechanical properties. After being added to the laminated wood, it can improve the cohesion and mechanical strength of the laminated wood. The epoxy resin, as an adhesive, has strong bonding force and can tightly bond wood powder and other materials together, thereby reducing wood waste and improving wood utilization to achieve environmental benefits, forming a laminated wood with stable structure and high strength. Through the curing and cross-linking reaction, a mesh structure can be formed, which further enhances the overall mechanical strength of the laminated wood. At the same time, the epoxy resin has good chemical corrosion resistance and can effectively resist the erosion of chemical substances such as acids, alkalis, and salts, so that the marine laminated wood can maintain stable performance even in a humid and corrosive environment, thereby ensuring that it is not easily damaged during use and extending its service life. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0033] Example 1

[0034] A composite preparation process for enhancing the mechanical properties of marine laminated wood comprises the following steps:

[0035] Step 1, ultrasonically disperse the basalt fiber in a mixed solvent, wherein the mixed solvent is a mixture of anhydrous ethanol and deionized water in a mass ratio of 4:1, and after uniform dispersion, add γ-aminopropyltriethoxysilane, wherein the mass ratio of the mixed solvent, basalt fiber, and γ-aminopropyltriethoxysilane is 2400:100:48, stir and mix, react at 25°C for 5h, filter after the reaction, wash with anhydrous ethanol, and dry at 60°C for 12h to obtain amino basalt fiber;

[0036] Step 2: Ultrasonically disperse nano titanium dioxide in N,N-dimethylformamide, and after uniform dispersion, add 1,8-diisocyanate and dibutyltin dilaurate, stir and mix, wherein the mass ratio of the added nano titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2100:95:1, react at 90°C for 10 hours, and after the reaction is completed, centrifuge at a rate of 8000r / min for 5 minutes, wash with anhydrous ethanol, and vacuum dry at 60°C for 8 hours to obtain isocyanate-modified titanium dioxide;

[0037] Step 3, ultrasonically dispersing the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, wherein the mass ratio of the aminated basalt fiber, isocyanate-modified titanium dioxide, and N,N-dimethylformamide is 100:72:2400, heating, reacting at 90°C for 9h, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain basalt fiber grafted titanium dioxide;

[0038] Step 4: Ultrasonic disperse the basalt fiber grafted titanium dioxide in N, N-dimethylformamide. After uniform dispersion, add p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine and mix evenly. The mass ratio of basalt fiber grafted titanium dioxide, N, N-dimethylformamide, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine is 100:3500:15:5:2:38. The reaction is carried out at 65° C. for 24 hours. After the reaction is completed, filter, wash with dichloromethane, and vacuum dry at 60° C. for 8 hours to obtain chloromethyl modified basalt fiber-titanium dioxide;

[0039] Step 5, ultrasonically disperse the chloromethyl modified basalt fiber-titanium dioxide in acetone, and after uniform dispersion, add dimethylaminoethyl methacrylate, wherein the mass ratio of chloromethyl modified basalt fiber-titanium dioxide, acetone, and dimethylaminoethyl methacrylate is 100:2100:48, heat up, react at 50°C, and react for 18 hours. After the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60°C for 8 hours to obtain antibacterial modified basalt fiber-titanium dioxide;

[0040] Step six, mix wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, calcium zinc composite stabilizer, and curing agent hexamethyltetramine in a mass ratio of 100:35:5:1:30, knead in an open mill, the kneading temperature is 120°C, the kneading time is 30 minutes, after mixing evenly, perform hot pressing in a hot press, the hot pressing temperature is 170°C, the hot pressing time is 8 minutes, and the hot pressing pressure is 8 MPa during the hot pressing process. After the hot pressing is completed, cool and demold to obtain marine laminated wood.

[0041] Example 2

[0042] A composite preparation process for enhancing the mechanical properties of marine laminated wood comprises the following steps:

[0043] Step 1, ultrasonically dispersing the basalt fiber in a mixed solvent, wherein the mixed solvent is a mixture of anhydrous ethanol and deionized water in a mass ratio of 4:1, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the mixed solvent, the basalt fiber, and the γ-aminopropyltriethoxysilane is 2800:100:50, stirring and mixing, reacting at 30°C for 3h, after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 60°C for 12h to obtain amino basalt fiber;

[0044] Step 2: Ultrasonic dispersion of nano titanium dioxide in N,N-dimethylformamide, after uniform dispersion, 1,8-diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred and mixed, wherein the mass ratio of the added nano titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2200:102:1.2, and the reaction is carried out at 95°C for 9 hours. After the reaction is completed, centrifugation is performed at a rate of 8000 r / min for 5 minutes, and then washed with anhydrous ethanol, and vacuum dried at 60°C for 8 hours to obtain isocyanate-modified titanium dioxide;

[0045] Step 3, ultrasonically dispersing the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, wherein the mass ratio of the aminated basalt fiber, isocyanate-modified titanium dioxide, and N,N-dimethylformamide is 100:80:2800, heating, reacting at 95°C for 7h, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain basalt fiber grafted titanium dioxide;

[0046] Step 4: ultrasonically disperse the basalt fiber grafted titanium dioxide in N,N-dimethylformamide, and after uniform dispersion, add p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine and mix evenly, wherein the mass ratio of basalt fiber grafted titanium dioxide, N,N-dimethylformamide, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine is 100:3800:18:6:4:45, react at 70°C, the reaction time is 20h, after the reaction is completed, filter, wash with dichloromethane, and vacuum dry at 60°C for 8h to obtain chloromethyl modified basalt fiber-titanium dioxide;

[0047] Step 5, ultrasonically disperse the chloromethyl modified basalt fiber-titanium dioxide in acetone, and after uniform dispersion, add dimethylaminoethyl methacrylate, wherein the mass ratio of chloromethyl modified basalt fiber-titanium dioxide, acetone, and dimethylaminoethyl methacrylate is 100:2300:52, heat up, react at 55°C, and react for 16 hours. After the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60°C for 8 hours to obtain antibacterial modified basalt fiber-titanium dioxide;

[0048] Step six, mix wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, calcium zinc composite stabilizer, and curing agent hexamethyltetramine in a mass ratio of 100:42:8:1.4:36, knead in an open mill, the kneading temperature is 125°C, the kneading time is 24 minutes, after mixing evenly, perform hot pressing in a hot press, the hot pressing temperature is 175°C, the hot pressing time is 6 minutes, and the hot pressing pressure is 8MPa during the hot pressing process. After the hot pressing is completed, cool and demold to obtain marine laminated wood.

[0049] Example 3

[0050] A composite preparation process for enhancing the mechanical properties of marine laminated wood comprises the following steps:

[0051] Step 1, ultrasonically disperse the basalt fiber in a mixed solvent, wherein the mixed solvent is a mixture of anhydrous ethanol and deionized water in a mass ratio of 4:1, and after uniform dispersion, add γ-aminopropyltriethoxysilane, wherein the mass ratio of the mixed solvent, basalt fiber, and γ-aminopropyltriethoxysilane is 3200:100:52, stir and mix, react at 30°C for 4h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry at 60°C for 12h to obtain amino basalt fiber;

[0052] Step 2: Ultrasonic dispersion of nano titanium dioxide in N,N-dimethylformamide, after uniform dispersion, 1,8-diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred and mixed, wherein the mass ratio of the added nano titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2400:110:1.5, and the mixture is reacted at 105°C for 9 hours. After the reaction is completed, the mixture is centrifuged at a rate of 8000 r / min for 5 minutes, and then washed with anhydrous ethanol, and vacuum dried at 60°C for 8 hours to obtain isocyanate-modified titanium dioxide;

[0053] Step 3, ultrasonically dispersing the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, wherein the mass ratio of the aminated basalt fiber, isocyanate-modified titanium dioxide, and N,N-dimethylformamide is 100:90:3000, heating, reacting at 100°C for 8h, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain basalt fiber grafted titanium dioxide;

[0054] Step 4: Ultrasonic disperse the basalt fiber grafted titanium dioxide into N, N-dimethylformamide. After uniform dispersion, add p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine and mix evenly. The mass ratio of basalt fiber grafted titanium dioxide, N, N-dimethylformamide, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine is 100:4200:24:8:5:55. The reaction is carried out at 70° C. for 22 hours. After the reaction is completed, filter, wash with dichloromethane, and vacuum dry at 60° C. for 8 hours to obtain chloromethyl modified basalt fiber-titanium dioxide;

[0055] Step 5, ultrasonically disperse the chloromethyl modified basalt fiber-titanium dioxide in acetone, and after uniform dispersion, add dimethylaminoethyl methacrylate, wherein the mass ratio of chloromethyl modified basalt fiber-titanium dioxide, acetone, and dimethylaminoethyl methacrylate is 100:2400:56, heat up, react at 55°C, and react for 16 hours. After the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60°C for 8 hours to obtain antibacterial modified basalt fiber-titanium dioxide;

[0056] Step six, mix wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, calcium zinc composite stabilizer, and curing agent hexamethyltetramine in a mass ratio of 100:42:8:1.4:36, knead in an open mill, the kneading temperature is 125°C, the kneading time is 24 minutes, after mixing evenly, perform hot pressing in a hot press, the hot pressing temperature is 175°C, the hot pressing time is 6 minutes, and the hot pressing pressure is 8MPa during the hot pressing process. After the hot pressing is completed, cool and demold to obtain marine laminated wood.

[0057] Example 4

[0058] A composite preparation process for enhancing the mechanical properties of marine laminated wood comprises the following steps:

[0059] Wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, calcium zinc composite stabilizer and curing agent hexamethyltetramine in a mass ratio of 100:52:10:1.8:45 were mixed evenly, kneaded in an open mill at a kneading temperature of 130°C and a kneading time of 28 minutes. After mixing evenly, hot pressing was performed in a hot press at a temperature of 175°C and a hot pressing time of 7 minutes. During the hot pressing process, the hot pressing pressure was 8 MPa. After the hot pressing was completed, the hot pressing was cooled and demolded to obtain marine laminated wood.

[0060] The preparation method of the antibacterial modified basalt fiber-titanium dioxide is the same as the preparation method of the antibacterial modified basalt fiber-titanium dioxide in Example 3.

[0061] Example 5

[0062] A composite preparation process for enhancing the mechanical properties of marine laminated wood comprises the following steps:

[0063] Step 1, ultrasonically dispersing the basalt fiber into a mixed solvent, wherein the mixed solvent is a mixture of anhydrous ethanol and deionized water in a mass ratio of 4:1, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the mixed solvent, the basalt fiber, and the γ-aminopropyltriethoxysilane is 3500:100:55, stirring and mixing, reacting at 35°C for 2h, after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 60°C for 12h to obtain amino basalt fiber;

[0064] Step 2: Ultrasonic dispersion of nano titanium dioxide in N,N-dimethylformamide, after uniform dispersion, 1,8-diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred and mixed, wherein the mass ratio of the added nano titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2500:115:1.6, and the reaction is carried out at 110°C for 8 hours. After the reaction is completed, centrifugation is performed at a rate of 8000 r / min for 5 minutes, and then washed with anhydrous ethanol, and vacuum dried at 60°C for 8 hours to obtain isocyanate-modified titanium dioxide;

[0065] Step 3: ultrasonically disperse the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, wherein the mass ratio of the aminated basalt fiber, isocyanate-modified titanium dioxide, and N,N-dimethylformamide is 100:95:3200, heat up, react at 105°C for 6h, filter after the reaction, wash with anhydrous ethanol, and vacuum dry at 60°C for 12h to obtain basalt fiber grafted titanium dioxide;

[0066] Step 4: Ultrasonic disperse the basalt fiber grafted titanium dioxide in N, N-dimethylformamide, and after uniform dispersion, add p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine and mix evenly, wherein the mass ratio of basalt fiber grafted titanium dioxide, N, N-dimethylformamide, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine is 100:4500:25:9:6:60, react at 75°C, the reaction time is 18h, after the reaction is completed, filter, wash with dichloromethane, and vacuum dry at 60°C for 8h to obtain chloromethyl modified basalt fiber-titanium dioxide;

[0067] Step 5, ultrasonically disperse the chloromethyl modified basalt fiber-titanium dioxide in acetone, and after uniform dispersion, add dimethylaminoethyl methacrylate, wherein the mass ratio of chloromethyl modified basalt fiber-titanium dioxide, acetone, and dimethylaminoethyl methacrylate is 100:2500:60, heat up, react at 60°C, and the reaction time is 15h. After the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60°C for 8h to obtain antibacterial modified basalt fiber-titanium dioxide;

[0068] Step six, mix wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, calcium zinc composite stabilizer, and curing agent hexamethyltetramine in a mass ratio of 100:55:12:2:48, knead in an open mill, the kneading temperature is 135°C, the kneading time is 15 minutes, after mixing evenly, perform hot pressing in a hot press, the hot pressing temperature is 180°C, the hot pressing time is 5 minutes, and the hot pressing pressure is 8MPa during the hot pressing process. After the hot pressing is completed, cool and demold to obtain marine laminated wood.

[0069] Comparative Example 1

[0070] A composite preparation process for laminated wood comprises the following steps:

[0071] Step 1, ultrasonically disperse the basalt fiber in a mixed solvent, wherein the mixed solvent is a mixture of anhydrous ethanol and deionized water in a mass ratio of 4:1, and after uniform dispersion, add γ-aminopropyltriethoxysilane, wherein the mass ratio of the mixed solvent, basalt fiber, and γ-aminopropyltriethoxysilane is 3200:100:52, stir and mix, react at 30°C for 4h, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry at 60°C for 12h to obtain amino basalt fiber;

[0072] Step 2: Ultrasonic dispersion of nano titanium dioxide in N,N-dimethylformamide, after uniform dispersion, 1,8-diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred and mixed, wherein the mass ratio of the added nano titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2400:110:1.5, and the mixture is reacted at 105°C for 9 hours. After the reaction is completed, the mixture is centrifuged at a rate of 8000 r / min for 5 minutes, and then washed with anhydrous ethanol, and vacuum dried at 60°C for 8 hours to obtain isocyanate-modified titanium dioxide;

[0073] Step 3, ultrasonically dispersing the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, wherein the mass ratio of the aminated basalt fiber, isocyanate-modified titanium dioxide, and N,N-dimethylformamide is 100:90:3000, heating, reacting at 100°C for 8h, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain basalt fiber grafted titanium dioxide;

[0074] Step 4: Mix wood powder, epoxy resin, Wuyan fiber grafted titanium dioxide, calcium zinc composite stabilizer, and curing agent hexamethyltetramine in a mass ratio of 100:52:10:1.8:45, knead in an open mill at a kneading temperature of 130°C and a kneading time of 28 minutes. After mixing evenly, perform hot pressing in a hot press at a temperature of 175°C and a hot pressing time of 7 minutes. During the hot pressing process, the hot pressing pressure is 8 MPa. After the hot pressing is completed, cool and demold to obtain laminated wood.

[0075] Comparative Example 2

[0076] A composite preparation process for laminated wood comprises the following steps:

[0077] Wood powder, epoxy resin, basalt fiber, nano titanium dioxide, calcium zinc composite stabilizer and curing agent hexamethyltetramine in a mass ratio of 100:52:5.3:4.7:1.8:45 were mixed evenly, kneaded in an open mill at a kneading temperature of 130°C and a kneading time of 28 min. After mixing evenly, hot pressing was performed in a hot press at a temperature of 175°C and a hot pressing time of 7 min. During the hot pressing process, the hot pressing pressure was 8 MPa. After the hot pressing was completed, the laminated wood was cooled and demolded.

[0078] Comparative Example 3

[0079] A composite preparation process for laminated wood comprises the following steps:

[0080] Wood powder, antibacterial modified basalt fiber-titanium dioxide, calcium-zinc composite stabilizer and curing agent hexamethyltetramine in a mass ratio of 152:10:1.8:45 were mixed evenly, kneaded in an open mill at a kneading temperature of 130°C and a kneading time of 28 minutes. After mixing evenly, hot pressing was performed in a hot press at a temperature of 175°C and a hot pressing time of 7 minutes. During the hot pressing process, the hot pressing pressure was 8MPa. After the hot pressing was completed, the laminated wood was cooled and demolded to obtain laminated wood.

[0081] The preparation method of the antibacterial modified basalt fiber-titanium dioxide is the same as the preparation method of the antibacterial modified basalt fiber-titanium dioxide in Example 3.

[0082] The basalt fiber used in the embodiments and comparative examples of the present invention was purchased from Zhejiang Shijin Basalt Fiber Co., Ltd., with a length of 6 mm and a diameter of 13 μm; nano titanium dioxide was purchased from Xuancheng Jingrui New Materials Co., Ltd., model JR05, and average particle size of 5 nm; epoxy resin is bisphenol A epoxy resin, purchased from China Nantong Xingchen Synthetic Materials Co., Ltd., brand WSR618 (E-51); stabilizer was purchased from Shenzhen Sende Plastic Additive Co., Ltd., which is CZX768 calcium zinc stabilizer; wood powder is poplar wood powder, produced in Siyang, Jiangsu, with an average density of 0.4 g / cm 3 ; Other reagents not specified are commercially available.

[0083] The laminated wood prepared in Examples 1-5 and Comparative Examples 1-3 was tested, and the test results are as follows:

[0084] (1) Mechanical properties test: Referring to GB / T 1447-2005 "Test method for tensile properties of fiber reinforced plastics", the tensile strength test of the samples was carried out using a HZ-1009A universal tensile testing machine, the test speed was 10 mm / min, and 3 samples were measured in each group and the average value was taken; referring to GB / T1449-2005 "Test method for flexural properties of fiber reinforced plastics", the flexural properties of the samples were tested using an XWW microcomputer-controlled electronic universal testing machine, the test speed was 2 mm / min, the span was 64 mm, and 3 samples were measured in each group and the average value was taken; the test results are shown in Table 1:

[0085] Table 1

[0086]

[0087] According to the test results in Table 1, it can be seen that the laminated wood corresponding to Examples 1-5 has excellent mechanical properties, and the tensile strength of the laminated wood corresponding to Example 5 can reach 280.2MPa and the bending strength can reach 216.5MPa. In Comparative Example 1, no quaternary ammonium salt was introduced into the basalt fiber grafted titanium dioxide, which had little effect on the mechanical properties of the laminated wood, and the corresponding tensile strength of the laminated wood could reach 279.5MPa and the bending strength could reach 217.0MPa; in Comparative Example 2, basalt fiber and nano-titanium dioxide were directly added to replace the antibacterial modified basalt fiber-titanium dioxide, and the dispersibility of nano-titanium dioxide and basalt fiber became poor, and the compatibility with the matrix was poor, and the mechanical properties were reduced, and the corresponding tensile strength could reach 221.7MPa and the bending strength could reach 174.2MPa; in Comparative Example 3, no epoxy resin was added, and the adhesion between the components became poor, and the mechanical properties were greatly reduced, and the corresponding tensile strength could reach 182.0MPa and the bending strength could reach 151.9MPa.

[0088] (2) Antibacterial performance test: The antibacterial performance of laminated wood was tested according to GB / T 4789.2-2010 "Determination of total bacterial count in food microbiology". The test bacteria were Escherichia coli and Staphylococcus aureus. The antibacterial rate was recorded. The test results are shown in Table 2:

[0089] Table 2

[0090]

[0091] According to the test results in Table 2, it can be seen that the laminated wood corresponding to Examples 1-5 has excellent antibacterial properties and can well inhibit the growth of Escherichia coli and Staphylococcus aureus. In Comparative Example 1, quaternary ammonium salt was not introduced into the basalt fiber grafted titanium dioxide, and the antibacterial properties of the laminated wood were greatly reduced; in Comparative Example 2, basalt fiber and nano-titanium dioxide were directly added to replace the antibacterial modified basalt fiber-titanium dioxide, and the dispersibility of nano-titanium dioxide and basalt fiber became poor, and the compatibility with the matrix was poor, and the antibacterial properties were reduced; in Comparative Example 3, epoxy resin was not added, which had a certain impact on the antibacterial properties.

[0092] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A composite preparation process for enhancing the mechanical properties of marine laminated wood, characterized in that: The steps include: Step 1: ultrasonically disperse the basalt fiber in a mixed solvent, add γ-aminopropyltriethoxysilane after uniform dispersion, stir and mix, react at 25-35°C for 2-5h, filter, wash, and dry at 60°C for 12h after the reaction to obtain amino basalt fiber; Step 2: Ultrasonically disperse nano-titanium dioxide in N,N-dimethylformamide, and after uniform dispersion, add 1,8-diisocyanate and dibutyltin dilaurate, stir and mix, react, and after the reaction is completed, centrifuge, wash, and vacuum dry at 60° C. for 8 hours to obtain isocyanate-modified titanium dioxide; Step 3: ultrasonically disperse the aminated basalt fiber and isocyanate-modified titanium dioxide in N,N-dimethylformamide, heat up, react, filter, wash, and vacuum dry at 60° C. for 12 h to obtain basalt fiber grafted titanium dioxide; Step 4: Ultrasonically disperse the basalt fiber grafted titanium dioxide in N,N-dimethylformamide. After uniform dispersion, add p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine, mix evenly, and react. After the reaction is completed, filter, wash, and vacuum dry at 60° C. for 8 hours to obtain chloromethyl-modified basalt fiber-titanium dioxide; Step 5: ultrasonically disperse the chloromethyl modified basalt fiber-titanium dioxide in acetone, add dimethylaminoethyl methacrylate after uniform dispersion, heat up, react, and after the reaction is completed, filter, wash, and vacuum dry at 60° C. for 8 hours to obtain antibacterial modified basalt fiber-titanium dioxide; Step 6: Evenly mix wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, stabilizer and curing agent, knead in an open mill, and after evenly mixing, perform hot pressing molding in a hot press, cool, and demold to obtain marine laminated wood; In the step six, the mass ratio of wood powder, epoxy resin, antibacterial modified basalt fiber-titanium dioxide, stabilizer and curing agent is 100:35-55:5-12:1-2:30-48.

2. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step 1, the mass ratio of the mixed solvent, basalt fiber and γ-aminopropyltriethoxysilane is 2400-3500:100:48-55.

3. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step 2, the mass ratio of nano titanium dioxide, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2100-2500:95-115:1-1.6, the reaction temperature is 90-110° C., and the reaction time is 8-10 hours.

4. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step three, the mass ratio of the amino basalt fiber, the isocyanate-modified titanium dioxide, and the N,N-dimethylformamide is 100:72-95:2400-3200.

5. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: The reaction temperature in step 3 is 90-105° C., and the reaction time is 6-9 hours.

6. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step 4, the mass ratio of basalt fiber grafted with titanium dioxide, N,N-dimethylformamide, p-chloromethylbenzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole, and triethylamine is 100:3500-4500:15-25:5-9:2-6:38-60, the reaction temperature is 65-75°C, and the reaction time is 18-24h.

7. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step 5, the mass ratio of chloromethyl modified basalt fiber-titanium dioxide, acetone, and dimethylaminoethyl methacrylate is 100:2100-2500:48-60, the reaction temperature is 50-60° C., and the reaction time is 15-18 hours.

8. The composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step 6, the kneading temperature in the open mill is 120-135° C., the kneading time is 15-30 min, the hot pressing temperature is 170-180° C., the hot pressing time is 5-8 min, and the hot pressing pressure is 8 MPa during the hot pressing process.

9. A composite preparation process for enhancing the mechanical properties of marine laminated wood according to claim 1, characterized in that: In the step six, the stabilizer is a calcium-zinc composite stabilizer, and the curing agent is hexamethyltetramine.

Citation Information

Patent Citations

  • Preparation method for anticorrosive antibacterial wood fiber composite

    CN109731747A

  • Preparation method of light epoxy resin substituted wood

    CN116218141A

  • Composite material type laminated wood for LNG (Liquefied Natural Gas) ship

    CN117844187A

  • Preparation method of lubricating resin composition

    CN116082837A

  • Metal organic framework composite antibacterial film and preparation method thereof

    CN116732783A

Cited By

  • Marine composite material laminated structure

    CN121515568A